Radiant fugitives : a novel - Ahmed, Nawaaz (Counterpoint, 2021)
"Raised in India, Seema is the beloved daughter of a commanding, erudite, Romantic-poetry-loving doctor father who cut her off when she came out to him as a lesbian. Now living alone in San Francisco, estranged from her African American ex-husband, Seema is one week away from delivering a baby boy, Ishraaq. Ishraaq's arrival has brought to Seema's side, for the first time in 15 years, her terminally ill mother, Nafeesa, and her devoutly religious, hijab-wearing sister Tahera, an ob/gyn living with her husband and two young children in Irving, Texas. But there is to be no easy reconciliation. Instead, this fateful week, narrated by the new-born Ishraaq, ends in an emergency delivery, revealing both a family and a country in distress. The characters confront the complex tensions in their relationships and within their innermost selves, even as their lives are upended by the vandalism of a family mosque in Irving during the lead-up to President Obama's first mid-term elections. Ishraaq must make sense of the broken family and the complicated world that awaits him"--